The Relationship of Academic Procrastination with Student Learning Outcomes of SMA N 2 Padang - Nia Chaliza Alifiar; Azrul Said (Universitas Negeri Padang, 2019)
This research is motivated by the fact that there are still students whose learning outcomes are low. one of the causes of low learning outcomes is academic procrastination. This study aims to see a picture of student learning outcomes, academic procrastination, and examine the relationship of academic procrastination with student learning outcomes.This type of research is descriptive correlational. The sample of this study was 256 students from 709 student populations in SMA N 2 Padang. Data analysis techniques using descriptive and correlational analysis techniques using the help of a computer program Statistics Product and Service Solution (SPSS) version 20.0. The instrument used was a Likert scale model questionnaire to measure academic procrastination.The research findings reveal (1) overall academic procrastination is in the medium category with a percentage (62.50%). (2) the delay aspect to start completing a task is in the low category with a percentage (48.4%), (3) the delay aspect in doing a task is in the medium category with a percentage (50.8%) (4) aspects of the time gap between plans and actual performance is in the medium category with a percentage (56.3%), (5) aspects of doing activities that are more enjoyable than doing the tasks that must be done are in the moderate category with a percentage (43.0%). (6) Student learning outcomes are generally in the quite good category with a percentage (43%). (7) there is a significant negative relationship between Academic Procrastination and Student Learning Outcomes